The Relationship of the Incident of Obesity and Early Providing MPASI to Babies at the Juli Puskemas Juli District, Bireuen District - Intan Mandira; Debi Novita Siregar; Gracetika Jeny Chlaudya Simanjuntak; Ika Lestari Siregar; Julia; Imtihani (JURNAL KEBIDANAN KESTRA (JKK), 2025)
Childhood obesity is defined as excessive accumulation of body fat, which can trigger various diseases. Exclusive breastfeeding is very important to prevent babies from gaining weight too quickly. The purpose of this study was to determine the relationship between obesity and early complementary feeding in infants. This study used an analytical approach with a cross-sectional study type. The sample in this study were respondents who met the established criteria. Sampling in this study used accidental sampling, with a sample of 42 respondents. The results showed that the majority of respondents were aged > 18 - 24 months, namely 14 respondents (33.33%) and were male, namely 25 respondents (59.52%). The majority of infants' weight was in the normal category, namely 41 respondents (97.62%). The majority of early complementary feeding was not given, namely 22 respondents (52.35%). Statistical analysis using Chi-square test obtained a value of ? (0.300) > ? (0.05), so there was no significant relationship between the provision of early complementary foods and the incidence of obesity in infants. The conclusion of this study is that there is no relationship between the incidence of obesity and the provision of early complementary foods. By increasing the knowledge of mothers about complementary foods through cooperation between educators and health institutions, it is expected to improve the nutritional quality of infants and support their optimal growth and development